Transposition of Ecclesiastical Ministry Paradigm in the Era Society 5.0 - Marbun, Tolop Oloan (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: Paradigm transposition in church ministry indicates the action of transposing the paradigm toward church ministry, especially during the COVID-19 pandemic. To stop the spread of COVID-19, churches must provide online services to serve their congregation better. Before the COVID-19 pandemic, many Christians disagreed with online church ministries. During the COVID-19 pandemic, they started accepting online church ministries and became accustomed to it. This transposition might be continued to Metaverse in Society 5.0. This research aims to show the transposition of the paradigm toward church ministry in Era Society 5.0. The method is qualitative research. The source of data is works of literature, surveys, and interviews. The analytic model is content analysis and descriptive-analytic. Since this is also descriptive research, all the analysis results are displayed descriptively. As a result, respondents experience the transposition of paradigms toward church ministry in Era Society 5.0. Transposition toward the online church, online service, online prayer and counseling, online sacraments, and community. The conclusion is that all respondents experienced all models of transposition.Â Keywords: Church Ministry; Metaverse; Paradigm Transposition; Society 5.0;